Dear Alben : Mr. Barkley of Kentucky. - Libbey, James K. (Kentucky Bicentennial bookshelf., 2009)
Alben Barkley's final words before he was struck down by a heart attack summed up his long, eventful life: ""I have served my country and my people for half a century as a Democrat. I went to the House of Representatives in 1913 and served fourteen years. I was a junior Congressman, then I became a senior Congressman, then I went to the Senate and became a junior Senator, and then I became a senior Senator; and then a Majority Leader in the Senate, and then Vice President of the United States, and now I am back again as a junior Senator. And I am willing to be a junior. I'm glad to sit in the.